Site-specific Umpolung amidation of carboxylic acids via triplet synergistic catalysis - Ning, Yunyun (Nat Commun, 2021)
Development of catalytic amide bond-forming methods is important because they could potentially address the existing limitations of classical methods using superstoichiometric activating reagents. In this paper, we disclose an Umpolung amidation reaction of carboxylic acids with nitroarenes and nitroalkanes enabled by the triplet synergistic catalysis of FeI(2), P(V)/P(III) and photoredox catalysis, which avoids the production of byproducts from stoichiometric coupling reagents. A wide range of carboxylic acids, including aliphatic, aromatic and alkenyl acids participate smoothly in such reactions, generating structurally diverse amides in good yields (86 examples, up to 97% yield). This Umpolung amidation strategy opens a method to address challenging regioselectivity issues between nucleophilic functional groups, and complements the functional group compatibility of the classical amidation protocols. The synthetic robustness of the reaction is demonstrated by late-stage modification of complex molecules and gram-scale applications.